2016
DOI: 10.1111/trf.13753
|View full text |Cite
|
Sign up to set email alerts
|

How do we manage blood product support in the massively hemorrhaging obstetric patient?

Abstract: Obstetric hemorrhage remains a leading cause of maternal mortality with more than 140,000 deaths annually worldwide. Abnormal placentation has increased to become the most common diagnosis requiring massive blood transfusion in obstetrics, with uterine atony a close second. At our institution, as well as nationwide, there has been a steady increase in pregnancies complicated by abnormal placentation, including accreta, increta, and percreta. Providers at our facility created the New England Center for Placenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
2
0
2
Order By: Relevance
“…Previous studies reported that the multiparous pregnancy had a higher risk for PPH than nulliparous pregnancy [ 6 , 8 , 13 , 15 , 16 , 19 , 39 ], when parity was included as one of the independent variables. This study shows that multiparous women have a greater risk for progression to severe PPH than nulliparous women if they received CS or forceps-assisted delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that the multiparous pregnancy had a higher risk for PPH than nulliparous pregnancy [ 6 , 8 , 13 , 15 , 16 , 19 , 39 ], when parity was included as one of the independent variables. This study shows that multiparous women have a greater risk for progression to severe PPH than nulliparous women if they received CS or forceps-assisted delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Most PPH-related studies about the difference between nulliparous and multiparous women are generally consistent in that compared with nulliparous, being multiparous would be a protective factor of PPH [ 6 , 8 , 13 , 15 19 ]. The reason behide this is perhaps that previous studies just analyzed their samples without considering the differential effects of delivery methods on the specific parturients that might be modified by parity, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Brzo obezbeĎivanje krvi i krvnih komponenti u ovim situacijama mogu biti od vitalnog značaja [3]. Najčešća urgentna stanja u kojima je potrebna efikasna transfuzija su: masivna akušerska krvarenja, pedijatrijske traume, neonatalna krvarenja, masivna gastrointestinalna krvarenja, urgentna stanja u hematologiji, trauma i dr. [4][5][6][7].…”
Section: Uvodunclassified
“…Многочисленные исследования показывают прямую зависимость между возрастающим количеством кесаревых сечений и случаев аномального прикрепления плаценты [3][4][5][6]. В настоящее время кесарево сечение является самой частой операцией в мире.…”
unclassified